Aerospace series. Steel FE-PM1503 (X3CrNiMoAl 13-8-2). Vacuum induction melted and consumable electrode remelted. Solution treated and precipitation treated. Bar for machining. a or D ≤ 150 mm. Rm ≥ 1 400 MPa. (29th January 2020) - British Standards Institution,
No abstract available